Microstructures and enhanced mechanical properties of (Al3Ti+Al2O3)/Al–Si composites with co-continuous network structure prepared by pressure infiltration. Issue 24 (15th December 2022) - He, Xiangxiang; Lin, Bo; Zhang, Wenxin; Xiao, Huaqiang; Zhang, Weiwen
Abstract: The (Al3 Ti + Al2 O3 )/Al–Si composites with three-dimensional co-continuous network structures are fabricated by a pore-forming agent and the pressure infiltration technique. The effect of the Al3 Ti content on the mechanical and wear properties of the developed composites is investigated. The Al2 O3 (alumina) formation, fracture, and wear mechanisms of the composites are also analyzed. The results demonstrate that the granular Al2 O3 particles scatter around Al3 Ti phases which are synthesized in-situ during the sintering process. The 20 vol.% (Al3 Ti + Al2 O3 )/Al–Si composites possess the optimal mechanical properties, i.e., compressive and flexural strength of 585 MPa and 489 MPa, respectively, which are 64.8% and 46.0% higher than those of the matrix. The specific wear rate of the composites (16.5 × 10 −14 m 3 /Nm) is 79% lower than that of the matrix. By further increasing the Al3 Ti content, the network structure is completed, the wear resistance properties are improved, while the mechanical properties are decreased. The enhanced mechanical properties can primarily be attributed to the three-dimensional co-continuous network structure of the Al3 Ti and Al2 O3 phases, as well as the pinning effect of Al2 O3 particles.